Systemic Risks: Theory and Mathematical Modeling. Issue 11 (27th August 2018) - Lucas, Klaus; Renn, Ortwin; Jaeger, Carlo
Abstract: In a globally connected world, new opportunities are associated with new types of risks. These new types of risks do not respect national boundaries nor are they restricted to particular locations or systems. Instead, they are characterized by contagion and proliferation processes, frequently on the basis of a network structure, with the result that a seemingly harmless local event is able to cause a complete system collapse. The proposal has been made to refer to these types of new risks as systemic risks. It turns out that key phenomena associated with systemic risks can quite naturally be categorized and analyzed in terms of notions originally established in the natural sciences, such as those of chaos, order, and self‐organization, or, more concisely, of dynamic structure generation in complex open systems. In this Essay, the claim is made that there is a homomorphism within the dynamic structure generation across very different domains of systemic risks. Furthermore, there are structural similarities between complex structures in general, and systemic risks in particular. Based on this assumption, one can use established methodologies of complexity science to reveal general macroscopic patterns that seem to govern the dynamics of complex systems. Abstract : The notion of systemic risks is a generic term describing phenomena of breakdown of whole systems macroscopically due to reinforcing feedback actions of agents on the microlevel. In this Essay, it is shown that complexity science provides a common theoretical basis of analyzing and mathematical modeling phenomena of systemic risks in widely different domains.